2010
DOI: 10.1007/s10745-010-9355-x
|View full text |Cite
|
Sign up to set email alerts
|

Wabusk of the Omushkegouk: Cree-Polar Bear (Ursus maritimus) Interactions in Northern Ontario

Abstract: In order to understand wabusk (polar bear, Ursus maritimus) behaviours and interactions with people in the Hudson Bay lowlands of northern Ontario we conducted this collaborative study of Cree kiskayndamowin/knowledge. Our findings reveal that Cree knowledge supports previously published information on polar bears, while adding further contextual findings: that male polar bears travel greater distances into the muskeg than previously recorded; that wabusk prey on amisk (beaver, Castor canadensis); that wabusk … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 47 publications
1
13
0
Order By: Relevance
“…Use of terrestrial foods by polar bears in the summer has commonly been reported in the literature for a number of populations (Russell, 1975;Derocher et al, 1993;Rockwell and Gormezano, 2009). Lemelin et al (2010) and Kakekaspan et al (2010) documented Cree observations of polar bears hunting beavers, and Slavik (2013) documented observations of polar bears scavenging on muskoxen, caribou, and grass in the Inuvialuit Settlement Region. Use of terrestrial foods was also previously reported for the CS population in Alaska (Kalxdorff, 1997).…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…Use of terrestrial foods by polar bears in the summer has commonly been reported in the literature for a number of populations (Russell, 1975;Derocher et al, 1993;Rockwell and Gormezano, 2009). Lemelin et al (2010) and Kakekaspan et al (2010) documented Cree observations of polar bears hunting beavers, and Slavik (2013) documented observations of polar bears scavenging on muskoxen, caribou, and grass in the Inuvialuit Settlement Region. Use of terrestrial foods was also previously reported for the CS population in Alaska (Kalxdorff, 1997).…”
Section: Discussionmentioning
confidence: 86%
“…By connecting past and present knowledge, documentation of Inuit qaujimajatuqangit (IQ, a term for TK used in Nunavut) in Canada has sought to capture trends in polar bear denning (Van de Velde et al, 2003), local polar bear abundance, and distribution over time, and to discover how unfolding processes of climate change may be affecting these trends (Dowsley, 2005;Keith et al, 2005;Kotierk, 2010a, b). Studies in other parts of Canada, including northwestern Ontario (Kakekaspan et al, 2010;Lemelin et al, 2010) and the Inuvialuit Settlement Region (Slavik, 2010(Slavik, , 2013, have likewise built on TK and human -polar bear interactions to contextualize current indigenous observations about polar bears. In Greenland, Born et al (2011) examined interrelated changes in ice conditions, polar bear abundance, growing polar bear catch, and shifting local hunting methods.…”
Section: Introductionmentioning
confidence: 99%
“…There is some limited information on polar bear TEK in the Southern Hudson Bay region based on a study conducted in the Ontario communities of Fort Severn and Peawanuck (Kakekaspan et al, 2010;Lemelin et al, 2010). However, little information has been compiled and published on the TEK of polar bear populations from the EMR communities in Québec (McDonald et al, 1997;Herrmann et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…We conducted semi-structured interviews with participants to document polar bear knowledge in the EMR. This interview method has proven appropriate in North American Arctic Indigenous groups (Ferguson and Messier, 1997;Huntington, 1998;Dowsley, 2007;Ferguson et al, 2012), as well as Cree communities in Ontario and Québec (Lemelin et al, 2010;Herrmann et al, 2012;Royer et al, 2013). The interview strategy is flexible and openended, and it allows for the expression of personal positions and beliefs.…”
Section: Methodsmentioning
confidence: 99%
“…polar bears (Lemelin et al 2010 ) and dugongs (Johannes and MacFarlane 1991 ), birds e.g. ivory gulls (Mallory et al 2003 ) and reptiles e.g.…”
Section: Providing Additional Information For Resource Managementmentioning
confidence: 99%